2020
DOI: 10.2147/ijn.s254344
|View full text |Cite
|
Sign up to set email alerts
|

<p>Multimodal Mesoporous Silica Nanocarriers for Dual Stimuli-Responsive Drug Release and Excellent Photothermal Ablation of Cancer Cells</p>

Abstract: Background: Core-shell types of mesoporous silica nanoparticles (MSNs) with multimodal functionalities were developed for bio-imaging, controlled drug release associated with external pH, and near-infrared radiation (NIR) stimuli, and targeted and effective chemo-photothermal therapeutics. Materials and Methods: We synthesized and developed a core-shell type of mesoporous silica nanocarriers for fluorescent imaging, stimuli-responsive drug release, magnetic separation, antibody targeting, and chemo-phototherma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 76 publications
0
19
0
Order By: Relevance
“…[12][13][14][15] ZIF8 possesses extra-high porosity, chemical and thermal stability, biocompatibility, and easily controllable size and shape. [16][17][18] Multifunctional ZIF8 nanomaterials have adaptability and responsiveness to various endogenous stimuli (e.g., pH, enzyme, and redox gradients) [19][20][21][22][23][24][25] and exogenous stimuli (e.g., temperature, magnetic eld, and light) [26][27][28][29] and controllable drug release for disease therapy and cell imaging. 24,30 Additionally, ZIF8 nanocarriers can have various nanomedicine applications, such as targeting cancer cells with hyaluronic acid conjugates, 31 magnetic resonance and uorescence imaging using uorescein isothiocyanate (FITC), 19 and controlled drug release by graphene oxide.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15] ZIF8 possesses extra-high porosity, chemical and thermal stability, biocompatibility, and easily controllable size and shape. [16][17][18] Multifunctional ZIF8 nanomaterials have adaptability and responsiveness to various endogenous stimuli (e.g., pH, enzyme, and redox gradients) [19][20][21][22][23][24][25] and exogenous stimuli (e.g., temperature, magnetic eld, and light) [26][27][28][29] and controllable drug release for disease therapy and cell imaging. 24,30 Additionally, ZIF8 nanocarriers can have various nanomedicine applications, such as targeting cancer cells with hyaluronic acid conjugates, 31 magnetic resonance and uorescence imaging using uorescein isothiocyanate (FITC), 19 and controlled drug release by graphene oxide.…”
Section: Introductionmentioning
confidence: 99%
“…The antibody was attached to the graphene oxide (GO) surface of MSNs composite. The result showed that with antibody conjugation, the carrier was internalized and retained in HeLa cells, and this indicated the effectiveness of the antibody in cancel targeting and treatment [ 139 ]. The FDA-approved antibody trastuzumab, which targets the HER2 receptor, was conjugated with MSNs to target breast cancer cells [ 140 , 141 , 142 ].…”
Section: Msns As Smart Drug Delivery Agentmentioning
confidence: 99%
“…Integrating multiple types of metallic/inorganic NPs into one unit enables synergistic enhancement in rational drug delivery, and consequently overcomes the limitations of conventional drug delivery platforms. Tran and coworkers fabricated a core–shell magnetic mSiO 2 NPs that comprise a Fe 3 O 4 core and a mSiO 2 coating with graft of fluorescent conjugates [ 78 ]. After drug loading and surface coating of polydopamine, they found further wrapping with graphene oxide layer and subsequent antibody functionalization exhibit more stable release behavior, active targeting feature, and dual stimuli-response to pH and near-infrared radiation (NIR), whereas coating with AuNPs layer will additionally support excellent photothermal therapy (PTT) due to nanoplasmonic effect [ 78 ].…”
Section: Rationality Of Nanoplatforms In Sepsis Managementmentioning
confidence: 99%
“…Tran and coworkers fabricated a core–shell magnetic mSiO 2 NPs that comprise a Fe 3 O 4 core and a mSiO 2 coating with graft of fluorescent conjugates [ 78 ]. After drug loading and surface coating of polydopamine, they found further wrapping with graphene oxide layer and subsequent antibody functionalization exhibit more stable release behavior, active targeting feature, and dual stimuli-response to pH and near-infrared radiation (NIR), whereas coating with AuNPs layer will additionally support excellent photothermal therapy (PTT) due to nanoplasmonic effect [ 78 ]. Similarly, ZnO quantum dots (QDs) with pH-responsive and gatekeeping features can be integrated into plasmonic AuNP@mSiO 2 nanocomposites, thus simultaneously enabling PTT and on-demand release of therapeutic doxorubicin (DOX) [ 79 ].…”
Section: Rationality Of Nanoplatforms In Sepsis Managementmentioning
confidence: 99%